Private Health Insurances as an Instrument Alleviating the Burden on Public Health Care System in Poland - Jeziorska, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article focuses on increasing demand for health services within polish national care system. It presents demographic, economic and social development context of this situation. The rules governing polish national care system are also demonstrated. The privet health insurances are indicated as an instrument alleviating the burden on public health care system. The data used come from Central Statistical Office of Poland and Eurostat.